2007
DOI: 10.1016/j.ijsolstr.2007.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Generalized layerwise mechanics for the static and modal response of delaminated composite beams with active piezoelectric sensors

Abstract: A coupled linear layerwise laminate theory and a beam FE are formulated for analyzing delaminated composite beams with piezoactuators and sensors. The model assumes zig-zag fields for the axial displacements and the electric potential and it treats the discontinuities in the displacement fields due to the delaminations as additional degrees of freedom. The formulation naturally includes the excitation of piezoelectric actuators, their interactions with the composite laminate, and the effect of delamination on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Delamination is predicted to start if The subscript 'i' stands for in-situ, while 't' and 'c' stand for traction and compression, respectively. This criterion does not take into consideration the transverse interlaminar stress σ 33 . However numerical tests in literature have shown that, in the majority of cases, this component has not a significant bearing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delamination is predicted to start if The subscript 'i' stands for in-situ, while 't' and 'c' stand for traction and compression, respectively. This criterion does not take into consideration the transverse interlaminar stress σ 33 . However numerical tests in literature have shown that, in the majority of cases, this component has not a significant bearing.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned in the introductory section, the most important feature by the viewpoint of accuracy and computational costs is whether the number of variables depends on the number of physical layers (see, e.g., Moreira and Rodrigues [32], Chrysochoidis and Saravanos [33], Hohe and Librescu [34], and Shariyat [35]) or it is fixed (see, e.g., Zhen and Wanji [17] and Icardi and Sola [25]). In the former case, accurate estimates are achieved at the expense of a high computational burden, while in the latter case complex algebraic manipulations are required in order to derive the expression of the unknowns as function of the d.o.f.…”
Section: Structural Modelmentioning
confidence: 99%
“…These research works have been extensively reviewed, among others, by Tay [17]. In parallel, simulation tools and/or damage criteria have been proposed and established for predicting interlaminar fracture initiation and propagation in composite materials, among others by Camanho, Davila and de Moura [18], Chrysochoidis and Saravanos [19], Sorensen and Jacobsen [20], Naghipour et al [21], Turon et al [22][23] and Goutianos and Sorensen [24], while relevant literature reviews have been conducted by Orifici, Herszberg and Thomson [25] and Mishnaevski and Brondsted [26]. The field of fracture modelling in composites has been continuously attracting attention up to date, as indicated by numerous book [27][28] and journal publications [29][30].…”
Section: Introductionmentioning
confidence: 99%
“…In a later work, Chrysochoidis and Saravanos [14] assessed the effects of delamination on the dynamic response of composite beam specimens with surface attached piezoelectric actuators and sensors using experiments and same analytical method developed earlier in [13]. Later, they developed an analytical model using coupled linear layerwise laminate theory and a FE model to investigate both static and dynamic response of flexible defective composite beams, including delaminations and active piezoelectric sensors [15]. Della and Shu [16,17] reported an analytical solution method, and more recently, Erdelyi and Hashemi used Dynamic Stiffness Matrix (DSM) [18] and presented a FEM-based novel assembly technique [19] to investigate the behaviour of a delaminated slender beam and compared their results with those reported by Wang et al [4] and Lee [20].…”
Section: Introductionmentioning
confidence: 99%